2019
DOI: 10.3389/fnut.2019.00128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic Supplementation on TGF-β1, TGF-β2, and IgA Levels in the Milk of Japanese Women: An Open-Label Pilot Study

Abstract: Background: Dietary probiotics supplementation in lactating mothers may help prevent allergic disease in infants. However, owing to a lack of consistency in nutritional and safety outcomes associated with probiotics, this topic remains controversial.Methods: In this open-label pilot trial conducted between April 2013 and December 2013, we evaluated the safety of probiotic supplementation with 5 × 109 CFU of Lactobacillus casei LC5, 5 × 109 CFU of Bifidobacterium longum BG7, and 2 × 108 CFU of Bacillus coagulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Among T cells, CD4 + CD25 + FOXP3 + T regs contain the main source of TGF-beta that suppresses immune responses in in ammatory sites [7,41]. In line with our ndings, some other studies showed the positive effects of probiotic administration on TFB-β concentration [6,42,43].…”
Section: Discussionsupporting
confidence: 88%
“…Among T cells, CD4 + CD25 + FOXP3 + T regs contain the main source of TGF-beta that suppresses immune responses in in ammatory sites [7,41]. In line with our ndings, some other studies showed the positive effects of probiotic administration on TFB-β concentration [6,42,43].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, dietary interventions may also alter breastmilk cytokines or immunoglobins; however, many results were inconclusive [179,192,193,194,195,196,197,198,199,200,201,202,203,204,205,206]. Several studies did not confirm the influence of fish oil or farmed salmon supplementation on breastmilk TGF-β1, TGF-β2, soluble cluster of differentiation (sCD14), and sIgA levels [179,200,201], but one study found that salmon consumption decreased sIgA levels [179].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Shermanii JS [206], whereas another study showed no effect from L. rhamnosus HN001 or B. lactis HN019 [204]. A decrease in TGF- β2 levels was shown after L. reuteri ATCC 55730 supplementation [203], but symbiotic supplementation resulted in its increase [195], and probiotic milk [196], L. rhamnosus HN001 [197] or L. casei LC5, B. longum BG7, and Bacillus coagulans SANK70258 [198] had no influence. No study, despite one investigating L. rhamnosus HN001 and B. lactis HN019 [204], confirmed the influence on TGF-β1 levels [195,196,197,198,203,207].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations